Study of the Relationship between P-Wave Dispersion and Left Ventricular Diastolic Dysfunction in Patients presenting to a Tertiary Care Centre of Western Region of Nepal - Sapkota , Subash; Paudel , Navaraj; Kafle, Ramchandra; Guragain, Sandeep; Tiwari , Ashok; Acharya, Chandra Prasad; Yadav , Alok (Nepal Journal of Medical Sciences, 2024)
Introduction: Left ventricular diastolic dysfunction (LVDD) leading to heart failure occurs when accompanied by a predominant or isolated abnormality in diastolic function in up to 50% of patients. Echocardiography remains primary investigation confirming diastolic dysfunction. This study emphasizes the use of P-wave dispersion (PWD) to assess and correlate with the diastolic dysfunction. Methods: This is a cross-sectional descriptive study conducted in the Department of Medicine (Cardiology Unit), Manipal Teaching Hospital from September 2023 to February 2024. After obtaining ethical clearance from IRC, participants who had echocardiographic evidence of LVDD were studied. Relevant data were collected in a preformed pro forma and statistical analyses were carried out. Results: Total 50 cases with 18 females and 32 males with mean age of 55.07 +/- 18.66 years was studied. There was strong association between increase in mean PWD with progression of LVDD from grade I to grade II, but not from grade II to grade III (P > 0.05). Progression of LVDD from grade I to grade III was associated with decrease in Left ventricular Ejection fraction (LVEF) (P value < 0.001). There was strong positive association between history of coronary artery disease (CAD) and increased PWD. Conclusions: Increase in PWD was associated with increasing grades of LVDD. PWD can be used as a predictive marker for early progression of disease from Grade I to II unlike from grade II to III. Progression of LVDD from grade I to III was associated with decrease in LVEF. Positive history of CAD was a significant risk factor for increased PWD associated with LVDD.